Aziridine-2-carboxaldehyde Dimers Undergo Homo-Ugi 4-Component-5-center Reactions - Rotstein, Benjamin H.; Yudin, Andrei K. (Synthesis, 2012)
Dimeric α-aziridine aldehydes have been used as the aldehyde component in Ugi and Passerini reactions. The highly reactive mixed anhydride intermediate is subject to nucleophilic attack by the aziridine, leading to ‘homo-Ugi’ β-acylaziridinyl-α-aminoamides. The products can be readily transformed into substituted lactones.
Keywords: aziridines; aldehydes; multicomponent reactions; heterocycles; amphoteric molecules